Aluminium honeycomb sandwich as a design alternative for lightweight marine structures. (3rd October 2022) - Palomba, G.; Epasto, G.; Sutherland, L.; Crupi, V.
ABSTRACT: Weight reduction and materials sustainability are becoming of primary importance for marine structures. A solution to both issues could lie in the application of all-metal sandwich structures. The study suggests the substitution of common marine structures with aluminium honeycomb sandwich structures (AHS), as a green and lightweight alternative, through a new methodology for structure comparison and design. Comparisons were based on bending stiffness equivalence and its relation to other design parameters, used to produce materials charts. A graphical approach based on plots of stiffness requirements, weight reduction goal and failure modes was applied for the identification of the main design variables. The feasibility and effectiveness of the developed approach was illustrated by outlining an example regarding the substitution of a GFRP-based ship balcony overhang with an equivalent AHS. The results showed the possibility to significantly reduce the weight, leave the geometry almost unchanged, and improve the mechanical response.